2011
DOI: 10.1248/cpb.59.120
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Hexylitaconates from a Marine Sponge-Derived Fungus Penicillium sp.

Abstract: Although dicarboxylic acids do not occur in appreciable amount as components of animal or vegetal lipids, generally they are important metabolic products of fatty acids. Especially the a,b-dicarboxylic acid and its derivatives, such as itaconic acid 1,2) and citraconic acid derivatives, 3) have been of much interest for their biosynthesis, stereochemistry, and chemical relationship. Furthermore, some of them were reported to exhibit various interesting bioactivities, such as plant growth-stimulation, 4) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
(34 reference statements)
2
19
0
1
Order By: Relevance
“…We used one-dimensional and two-dimensional NMR spectra to elucidate the structure of the two major metabolites produced by strain SP1: hexylaconitic acid and hexylitaconic acid (Supplemental information, Section on structural elucidation). Structures of the other compounds were determined by comparing their 1 H-and 13 C-NMR spectra with the major hexylaconitic acid and hexylitaconic acid, and with published data 24,[26][27]38 . Since all compounds in this study are derivatives of either hexylaconitic acid or hexylitaconic acid, we designate the major compounds as hexylaconitic acid A and hexylitaconic acid A.…”
Section: Nuclear Magnetic Resonance (Nmr) Analysis Reveals Seven Alkymentioning
confidence: 99%
See 4 more Smart Citations
“…We used one-dimensional and two-dimensional NMR spectra to elucidate the structure of the two major metabolites produced by strain SP1: hexylaconitic acid and hexylitaconic acid (Supplemental information, Section on structural elucidation). Structures of the other compounds were determined by comparing their 1 H-and 13 C-NMR spectra with the major hexylaconitic acid and hexylitaconic acid, and with published data 24,[26][27]38 . Since all compounds in this study are derivatives of either hexylaconitic acid or hexylitaconic acid, we designate the major compounds as hexylaconitic acid A and hexylitaconic acid A.…”
Section: Nuclear Magnetic Resonance (Nmr) Analysis Reveals Seven Alkymentioning
confidence: 99%
“…To identify the candidate cis-aconitate decarboxylase, we examined orthologous gene clusters predicted to be involved in alkylcitric acids biosynthesis. Previous reports have shown that alkylcitric acids and the similar structured maleidrides are being produced not only in A. niger but also in other filamentous fungi including Penicillium striatosporum 27,41 and A. oryzae 42 . Therefore, we used the alkylcitric acid cluster of A. niger as query to search for orthologous gene clusters in the published Aspergilli genomes.…”
Section: Analysis Of Orthologous Alkylcitric Acid Gene Clusters Reveamentioning
confidence: 99%
See 3 more Smart Citations